Upper Versus Lower Gastrointestinal Delivery for Transplantation of Fecal Microbiota in Recurrent or Refractory Clostridium difficile Infection: A Collaborative Analysis of Individual Patient Data From 14 Studies. Issue 2 (February 2017) - Furuya-Kanamori, Luis; Doi, Suhail A.R.; Paterson, David L.; Helms, Stefan K.; Yakob, Laith; McKenzie, Samantha J.; Garborg, Kjetil; Emanuelsson, Frida; Stollman, Neil; Kronman, Matthew P.; Clark, Justin; Huber, Charlotte A.; et al.
Abstract : Goals: The aim of this study was to compare upper gastrointestinal (UGI) versus lower gastrointestinal (LGI) delivery routes of fecal microbiota transplantation (FMT) for refractory or recurrent/relapsing Clostridium difficile infection (CDI). Background: FMT has been proven to be a safe and highly effective therapeutic option for CDI. Delivery, however, could be via the UGI or LGI routes, and it is unclear as to which route provides better clinical outcome. Study: A systematic search for studies that reported the use of FMT for CDI treatment was conducted. Individual patient data that included demographic (age and sex) and clinical (route of FMT delivery, CDI outcome after FMT, and follow-up time) information were obtained. Kaplan-Meier cumulative hazard curves and Cox proportional hazard models were used to assess clinical failure after FMT by the route of delivery. Results: Data from 305 patients treated with FMT (208 via LGI route and 97 via UGI route) for CDI were analyzed. At 30 and 90 days, the risk of clinical failure was 5.6% and 17.9% in the UGI group compared with 4.9% and 8.5% in the LGI delivery route group, respectively. A time-varying analysis suggested a 3-fold increase in hazard of clinical failure for UGI delivery (hazard ratio, 3.43; 95% confidence interval, 1.32-8.93) in the period after 30 days. Conclusions: FMT delivered via the LGI seems to be the most effective route for the prevention of recurrence/relapse of CDI. A randomized controlled trial is necessary to confirm whether FMT delivered via the LGI is indeed superior to that delivered via the UGI route. Abstract : Supplemental Digital Content is available in the text.